Pelatihan Literasi Budaya Terintegrasi Kepribadian Humanisme di SDN Made IV Lamongan - Oriza Zativalen; Ari Susandi; Vivi Yusnita Putri (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The aim of implementing this training is primarily to produce quality teachers by carrying out cultural literacy training activities integrated with humanist personality at SDN Made IV Lamongan. With this training activity, it is hoped that it can provide knowledge and information to teachers to increase cultural literacy in teaching in an independent curriculum with a humanist personality. This is a solution to various kinds of learning problems in the independent curriculum. The training targets who will be involved in this activity are all teachers at SDN Made IV Lamongan. The method that will be used is the training planning stage for grade 1 and 4 teachers by preparing cultural literacy and humanism personality activities. The second stage is the implementation of integrated cultural literacy training on humanism personality. The third stage is evaluation and follow-up to differentiate the results from the pretest and posttest. said to be successful and considered good. The results of community service that have been carried out, namely the success of implementing community service activities, apart from being measured from the components above, can also be seen from participant satisfaction after participating in training activities. The school is very satisfied with the activities provided by the service team because they provide significant benefits, including: increasing knowledge about cultural literacy and humanistic personality. The implementation of community service activities has been carried out well. The service material is cultural literacy training integrated with humanism personality at SDN Made IV Lamongan. Follow up by providing regular monitoring of the implementation of cultural literacy in learning. The final stage is publishing scientific work on community service.